Upaya meningkatkan aktivitas dan penguasaan huruf hiragana melalui team games tournament (TGT) berbasis kartu read and punishment - Ni Komang Andayani (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
This study is aimed to increase learning activity and mastery of hiragana letters for students through the application of cooperative learning with Team Games Tournament (TGT) based on Read and Punishment Card. The study was held on 8 January to March 2019. The subject is 32 Grade X students of language major in the second semester of SMA Negeri 1 Kuta Selatan in the academic year 2018/2019 and the objects are the learning activity and the mastery of hiragana letters of the students. The data of this research were analysed by descriptive quantitative method that was collected not only from the average of the students’ scores based on the individual or classical result of the test but also from the learning activity of the students during the learning process. The result shows that there is improvement in the learning activity and the mastery of hiragana letter of the students. The learning activity increases by 18.75% from the first cycle and the mastery of the hiragana letter also increases by 12.5% from the first cycle. Penelitian ini bertujuan untuk meningkatkan aktivitas dan penguasaan huruf hiragana siswa melalui penerapan model pembelajaran kooperatif tipe Team Games Tournament (TGT) berbasis kartu Read and Punishment. Penelitian ini dilaksanakan pada tanggal 8 Januari sampai dengan tanggal 26 Maret 2019. Subjek penelitian terdiri atas 32 orang siswa kelas X jurusan bahasa semester II SMA Negeri 1 Kuta Selatan tahun pelajaran 2018/2019 dan objek penelitian meliputi aktivitas dan penguasaan huruf hiragana siswa. Data dianalisis dengan metode deskriptif kuantitatif yang diperolah dari nilai rata-rata hasil tes baik klasikal maupun individual dan menganalisis aktivitas belajar siswa selama proses pembelajaran. Hasil penelitian menunjukkan adanya peningkatan aktivitas dan penguasaan huruf hiragana siswa. Aktivitas belajar siswa dalam proses pembelajaran terjadi peningkatan sebesar 18,75% dari siklus I dan peningkatan penguasaan huruf hiragana siswa sebesar 12,5% dari siklus I.